The Potential of Virtual Reality for Inducing Neuroplasticity in Children with Amblyopia - María B. Coco-Martin; David P. Piñero; Luis Leal-Vega; Carlos J. Hernández-Rodríguez; Joaquin Adiego; Ainhoa Molina-Martín; Dolores de Fez; Juan F. Arenillas (Journal of Ophthalmology)
In recent years, virtual reality (VR) has emerged as a new safe and effective tool for neurorehabilitation of different childhood and adulthood conditions. VR-based therapies can induce cortical reorganization and promote the activation of different neuronal connections over a wide range of ages, leading to contrasted improvements in motor and functional skills. The use of VR for the visual rehabilitation in amblyopia has been investigated in the last years, with the potential of using serious games combining perceptual learning and dichoptic stimulation. This combination of technologies allows the clinician to measure, treat, and control changes in interocular suppression, which is one of the factors leading to cortical alterations in amblyopia. Several clinical researches on this issue have been conducted, showing the potential of promoting visual acuity, contrast sensitivity, and stereopsis improvement. Indeed, several systems have been evaluated for amblyopia treatment including the use of different commercially available types of head mounted displays (HMDs). These HMDs are mostly well tolerated by patients during short exposures and do not cause significant long-term side effects, although their use has been occasionally associated with some visual discomfort and other complications in certain types of subjects. More studies are needed to confirm these promising therapies in controlled randomized clinical trials, with special emphasis on the definition of the most adequate planning for obtaining an effective recovery of the visual and binocular function.